Health in the city : race, poverty, and the negotiation of women's health in New York City, 1915-1930 - Hart, Tanya, 1956- (Culture, labor, history., 2015)
""At the turn of the twentieth century, black and white women migrated to New York City, a new place and environment swirling with ideas and practices of race, racism, germ theory and sanitation. Health in the City tells us the very human story of how pioneering, yet racialized health care thinking and services complicated the meaning of these women's motherhood as well as their own health and welfare. Hart's discovery and analysis of previously untapped archival records, offers an important narrative and reveals a remarkable mastery of historical methods that are a model of interdisciplinary.